‘I can’t pray’ – The spiritual needs of Malaysian Muslim patients suffering from depression - Md Rosli, Ahmad Nabil; SM, Saini; N, Nasrin; R, Bahari; S, Sharip (International Islamic University Malaysia., 2016)
Introduction: The mainstay of treatment of depression relies on pharmacological and psychological treatments. On top of that, evidence also recognizes the vital role of spirituality for human wellness which leads to growing interest in its utilization to treat depression. However, research on spirituality among Muslims in relation to depression is relatively scarce. The aim of this study is to explore the understanding of spirituality among Muslim patients with depression, and to explore their spiritual needs. Methods: This is a qualitative study conducted on 10 depressed Muslim patients at the UKM Medical Centre. Purposive sampling was done to ensure diversity of subjects. Individual in-depth interviews were conducted using semi-structured questionnaire guidelines. The data were transcribed verbatim and analysed using a thematic approach. Result: Out of 10 patients, almost all of them expressed spiritual needs. Two major themes emerged in relation to the spiritual needs which are (i) religious needs; need for worship, religious knowledge and guidance, religious reminders, and (ii) existential needs; need for calmness, sensitivity and empathy, self-discipline, certainty, hope , physical help, ventilate and meaning of illness. These needs are essential for patients during the time of crisis. Conclusion: The majority of patients expressed spiritual needs which are required during the process of recovery and this provides an opportunity to incorporate spiritual approaches in the treatment of depression. However, more studies are needed to demonstrate its scientific basis and to design an effective psycho-spiritual treatment modality so that the ‘holistic’ or ‘bio-psychosocial-spiritual’ treatment can be integrated by health care professionals to those in need.